Achieving guideline-based asthma control: does the patient benefit? - Bateman, E D; Frith, L F; Braunstein, G L (The European respiratory journal, 2002)
Asthma management guidelines define asthma control, but the outcome criteria used do not include the patient's own assessment of their health. The objective of the present study was to determine the association between the achievement of asthma control, as defined by the Global Initiative for Asthma (GINA) guidelines, and patient-assessed asthma-related quality of life (QOL), particularly whether maximal or near-maximal QOL scores were attainable. Clinical data from three studies that compared salmeterol/fluticasone propionate combination therapy (SFC) with other treatments in patients with persistent asthma were retrospectively analysed. Achievement of asthma control was determined over an 8-week period in each study according to six parameters derived from the GINA guideline treatment goals. Asthma Quality of Life Questionnaire (AQLQ) scores (a 7-point scale, where 1=severe impairment and 7=no impairment) were analysed by treatment group for well-controlled and not well-controlled patients. The analysis showed that, across a range of severities, well-controlled asthma patients had consistently higher AQLQ scores at endpoint and larger AQLQ improvements from baseline, than patients who were not well controlled. For many well-controlled patients, endpoint scores approached 7, indicating little or no impact of asthma on their QOL. However, AQLQ scores of not well-controlled patients also improved substantially in some treatment groups, particularly the SFC group. These results suggest a relationship between the achievement of guideline-based asthma control and improvements in quality of life to levels where there is little or no impact of asthma on quality of life. Guideline-based asthma control is therefore beneficial to the patient and should be tested in prospective studies.